2016
DOI: 10.1017/s1754470x16000076
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of IAPT psychological well-being practitioners’ intention to use CBT self-help materials routinely in their clinical practice

Abstract: BACKGROUND: Despite efficacy and effectiveness evidence, and recommendations from the National Institute for Health and Care Excellence (NICE), use of CBT self-help materials remains inconsistent in UK mental health services. Since 2006, the Improving Access to Psychological Therapies (IAPT) programe provides standardised training and mandates routine use of CBT self-help materials by their trainee psychological well-being practitioners (PWPs).AIMS: This study tested whether the main constructs of the theory o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Consistent with the Theory of Planned Behavior, 21 greater self-help intentions were predicted by greater positive attitudes, self-efficacy, and normative beliefs about self-help as well as knowledge of self-help resources. This is consistent with previous research in other populations for ehealth more broadly, 22,23 but is the first study to examine these factors with college student mental health specifically. Future research seeking to increase the adoption of self-help resources among college students might evaluate interventions to improve knowledge of effective self-help resources, attitudes towards self-help 27 or normative beliefs about treatment.…”
Section: Commentsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with the Theory of Planned Behavior, 21 greater self-help intentions were predicted by greater positive attitudes, self-efficacy, and normative beliefs about self-help as well as knowledge of self-help resources. This is consistent with previous research in other populations for ehealth more broadly, 22,23 but is the first study to examine these factors with college student mental health specifically. Future research seeking to increase the adoption of self-help resources among college students might evaluate interventions to improve knowledge of effective self-help resources, attitudes towards self-help 27 or normative beliefs about treatment.…”
Section: Commentsupporting
confidence: 89%
“…Previous research suggests that variables indicated in the Theory of Planned Behavior 21 are predictive of intentions to use online self-help including normative beliefs, attitudes, and self-efficacy. 22,23 Thus, we Does self-help minimize stigma? 6 predicted that lower self-efficacy, attitudes, knowledge, and normative beliefs regarding selfhelp would all relate to lower intentions to use self-help.…”
mentioning
confidence: 99%
“…The Theory of Planned Behavior (TPB; Ajzen, 2005 ) is a useful model for explaining clinician behaviors ( Eke et al, 2012 ; Levy et al, 2016 ; Lecomte et al, 2018 ). TPB proposes three main drivers of intention to perform an action: attitudes -comprising the imagined outcome of the action and how much that outcome is valued; subjective norms -comprising perceptions of what others would usually do and what they would approve or disapprove of doing, and how important that is to the person planning an action; and perceived behavioral control -comprising internal (e.g., self-efficacy for the action) and external facilitators and barriers (e.g., other duties that may need to be performed at a given time).…”
Section: Introductionmentioning
confidence: 99%